ChemInform Abstract: Direct Arylation of Sydnones with Aryl Chlorides Toward Highly Substituted Pyrazoles. Issue 27 (18th June 2015) - Brown, Andrew W.; Harrity, Joseph P. A.
Abstract The direct Pd‐catalyzed arylation of C‐4 unsubstituted sydnones by using aryl chlorides and bromides as coupling partners is developed.